Assessment of governance in the implementation of the SDGs: Bibliographic survey of theoretical contributions to the theme (2015-2021) (Research, Society and Development, 2022)
Concern about the future of the planet has awakened, in recent years, the need for change in the face of the current form of interaction between man and the environment, encompassing economic, social, environmental and institutional factors. In this sense, the UN and its member countries defined the Sustainable Development Goals (SDGs) in 2015, outlining in the 2030 Agenda an action plan for the next 15 years. However, the implementation of these objectives requires an effort aimed at transforming today's thinking and, consequently, attitudes that aim at planetary sustainability. The 2030 Agenda cites governance as a fundamental factor for sustainable development and in the implementation of these goals, indicating the need to assess possible progress and obstacles. Aiming to map works that approach the evaluation of governance in the implementation of the SDGs, as well as in other areas, to provide theoretical support and contributions to future research directed to the SDGs, a survey of articles was carried out in the Scopus and Web of Science databases in order to resolve the following question: how often does the approach to issues related to governance reach the discussion about the SDGs? There was a gap aimed at works that addressed the assessment of governance in the implementation of the SDGs in an integrated manner. However, even in small numbers, practical and theoretical studies of great contribution towards the evaluation of governance were also identified.